Frequency and Risk Factors of Dry Eye Disease in Pakistani Population, A Hospital Based Study - Ayub, Abdullah; Akhtar, Faryal Muhammad; Saleem, Najeeha; Ali, Muhammad Hassaan; Ayub, Muhammad Hammad; Butt, Nadeem Hafeez (Pakistan Journal of Ophthalmology, 2017)
Purpose: To determine prevalence and risk factors of dry eye in hospital based Pakistani population. Study Design: Cross-sectional study Place and Duration of Study: Department of Ophthalmology, Jinnah Hospital, Lahore.From April 2016 to June 2016. Materials and Methods: Three hundred cases above 18 years of age who presented to out-patient department with various ophthalmic complaints were enrolled in the study. Patients with acute inflammatory conditions, acute infections, gross corneal or conjunctival diseases, contact lens wearers and those who had gone any form ocular surgery within the last 6 months were excluded from the study. After taking detailed history, a pre-designed questionnaire was administered to the patients that inquired about various symptoms of dry eyes followed by a detailed ophthalmic assessment and measurement of tear film breakup time (TBUT) using fluorescein dye. Patients exhibiting TBUT < 10 seconds were labelled as dry eye sufferers. The likelihood ratio was used to calculate the p-values using Pearson Chi-square tests. Associations of environmental risk factors with dry eye was assessed using regression analysis. The strength of association of environmental factors with dry eyes was found by calculating odd’s ratio. RESULTS There were 300 participants enrolled in the study with mean age 46.8 ± 8.3 years. 54.3% were female patients in the study. The prevalence of dry eye was found to be 18.7%. Patients aged more than 70 years showed significantly higher prevalence of dry eyes (p = 0.006). 18.9% hypermetropes, 16.2% myopes and 15.2% emmetropes suffered from dry eyes. Multivariate regression analysis showed that outdoor workers, people working in air conditioners, housewives, diabetics, smokers, people exposed to excessive sunlight, wind, temperature, and patients suffering from meibomian gland dysfunction were at higher risk of developing dry eye. CONCLUSION Dry eye is associated with increasing age, female gender, outdoor occupations, smoking, diabetes, meibomian gland dysfunction and refractive errors.